1993
DOI: 10.1111/j.1365-2133.1993.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Capillary underperfusion in chronic venous insufficiency: a cause for leg ulceration?

Abstract: Dermal capillaries in the goiter area of the lower leg were examined by video-microscopy before and after the administration of intravenous fluorescein in 13 patients with chronic venous insufficiency (CVI) who were at risk of developing leg ulceration, and in 13 normal controls. The influence of posture on capillary perfusion was determined by viewing the same area of skin with the leg in both the supine and dependent positions. Capillary density was lower in patients than in controls, irrespective of the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…The disturbance of the blood flow regulation presented here applies mainly to the deeper layers of the skin circulation because of the limitations of laser Doppler fluxmetry. But by means of capillaroscopy it was recently shown that the reduction of the postural response also affects the nutritive compartment of cutaneous circulation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of the blood flow regulation presented here applies mainly to the deeper layers of the skin circulation because of the limitations of laser Doppler fluxmetry. But by means of capillaroscopy it was recently shown that the reduction of the postural response also affects the nutritive compartment of cutaneous circulation [21].…”
Section: Discussionmentioning
confidence: 99%
“…During cutaneous wound healing, the development of granulation tissue requires the formation of new capillaries, and the absence of this tissue is a typical feature of chronic nonhealing wounds (Luetolf et al, 1993;Bollinger et al, 1997). Local mechanisms leading to impaired angiogenesis in chronic non-healing wounds are poorly understood.…”
Section: Increased Levels Of the Soluble Variant Of The Vascular Endomentioning
confidence: 99%
“…It is now accepted that there is a decrease in the total num ber of capillaries in the affected area of skin around the ankle, associated with an increase in their tortuosity [1,2]. Interstitial oedema, resulting from changes in capillary permeability and haemorheological alterations, is a con stant feature of chronic venous insufficiency.…”
Section: Orphological Changesmentioning
confidence: 99%